A novel wideband erbium-doped fiber amplifier design - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Poopalan, P.; Selvakennedy, S.; Ahmad, Harith (John Wiley & Sons, 2000)
A novel wideband erbium-doped fiber amplifier utilizing a bidirectional amplification of conventional- and long-wavelength band signals is presented. Amplification of a four-channel wavelength-division multiplexing system (two channels for each band) is successfully demonstrated with an average gain of 20 dB and a noise figure less than 7.5 dB. (C) 2000 John Wiley & Sons, Inc.